2015
DOI: 10.1099/jmm.0.000028
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, outcomes and epidemiology associated with Clostridium difficile infection in patients with haematological malignancies in a tertiary care hospital in China

Abstract: The purpose of this study was to evaluate the risk factors, outcomes and epidemiology associated with Clostridium difficile infection (CDI) in patients with haematological malignancies in a tertiary care hospital in China. C. difficile screening was performed on patients admitted for chemotherapy or haematopoietic stem cell transplantation between 2009 and 2013. C. difficile isolates were analysed by multilocus sequence typing, and a retrospective chart review was performed on all patients with a positive toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…It was the first study to directly compare CDI outcomes after metronidazole, vancomycin, or combination therapy in patients with hematologic malignancies; 18.7% of patients (73/390) had CDI compared to the 7.0% of patients in the aforementioned study [35]. Similar results were concluded by Gu et al in 2015, who studied patients undergoing chemotherapy for haematological malignancies; 21% (21/97) of patients were diagnosed with CDI [36]. Some of the differences in reported incidence among these studies could be due to changing diagnostic algorithms over time.…”
Section: Immunodeficiency and The Implications For CDIsupporting
confidence: 63%
See 2 more Smart Citations
“…It was the first study to directly compare CDI outcomes after metronidazole, vancomycin, or combination therapy in patients with hematologic malignancies; 18.7% of patients (73/390) had CDI compared to the 7.0% of patients in the aforementioned study [35]. Similar results were concluded by Gu et al in 2015, who studied patients undergoing chemotherapy for haematological malignancies; 21% (21/97) of patients were diagnosed with CDI [36]. Some of the differences in reported incidence among these studies could be due to changing diagnostic algorithms over time.…”
Section: Immunodeficiency and The Implications For CDIsupporting
confidence: 63%
“…administration, the nanoparticle vaccine offered full protection from C. difficile, and provided long lasting Ab titers against antigen, compared to aluminum adjuvanted rTcdB [45]. Hong and colleagues developed a Bacillus subtilis spore-based oral vaccine consisting of a specific region of TcdA CBD (TcdA [26][27][28][29][30][31][32][33][34][35][36][37][38][39] ) and tested its efficacy in a hamster model. Hamsters immunized with the oral vaccine and challenged with C. difficile developed anti-TcdA CBD mucosal Abs that prevented colonization of C. difficile.…”
Section: Active Immunization Against C Difficilementioning
confidence: 99%
See 1 more Smart Citation
“…Cephalosporins, fluoroquinolones, clindamycins and ampicillins are those antimicrobials that are usually employed for C. difficile-associated diseases. Recent studies reported that the improper antibiotic use was the cause of increasing infections of C. difficile [28] .…”
Section: Difficilementioning
confidence: 99%
“…Inanimate objects and infected intestinal patients are major sites acted as reservoirs. Hospital staff along with hospital settings are also playing their part to a greater extent [28].…”
Section: Difficilementioning
confidence: 99%